Pengaruh Kemampuan Kapabilitas Dinamis Rantai Pasok pada Kinerja Perusahaan Kedai Kopi di Kota Tangerang Selatan - Ramadhan, Arlen Verta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the influence of supply chain dynamic capabilities on the performance of coffee shop companies in South Tangerang City. An effective and efficient supply chain is an important factor in achieving a competitive advantage in the growing coffee shop industry. to analyze the data obtained from a survey conducted on a number of coffee shops in South Tangerang City, the regression method was used. The independent variable used in this study is supply chain dynamic capabilities, while the dependent variable is the performance of coffee shop companies. The data collected was analyzed to examine the relationship between the variables. The results of this study indicate that supply chain dynamic capabilities have a significant positive effect on the performance of coffee shop companies in South Tangerang City. In conclusion, this study provides important insights into the relationship between supply chain dynamic capabilities and coffee shop company performance. The results of this research can be a basis for coffee shop companies to improve their ability to dynamically manage supply chains in order to achieve competitive advantage and better performance. Keywords: Coffee Shop, Capability, Supply Chain